HUBUNGAN KONDISI IKLIM ORGANISASI, TINGKAT SELF DISCLOSURE ANTARA PEMAIN DAN PELATIH DENGAN TINGKAT PRESTASI PEMAIN TERANGBANGSA FC U-18 - Irvian Izhar Fadilla; Hedi Pudjo Santosa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
To achieve a good achievement in an organization or a football club, a good organizational climate condition and interpersonal communication between players and players, players with coaches are also needed, one of that is self disclosure. Players in a team always need good organizational climate conditions, because when players feel comfortable in a team, players will be more free to show the abilities that they have so the team achievements will be achieved. Likewise with self disclosure, when players and coaches are open to each other about things on the field or outside the field, players will feel comfortable in a team so they are able to achieve achievements and targets that given by the team. This study aims to determine the relationship of organizational climate conditions, the level of self disclosure with the level of achievement of Terangbangsa FC U-18 players. In determining the hypothesis to be used, this study uses McClelland's Needs Theory and Personality Theory from several previous research journals. To determine the sample, this study uses a random sampling technique by means of simple random sampling. The number of samples studied amounted to 38 people with the characteristics of players who were officially registered with the club Terangbangsa FC U-18. The analysis of the data that used in this study is Kendall's tau-b. The results of the first hypothesis test show that there is a relationship between organizational climate conditions and the level of achievement of Terangbangsa FC U-18 players with a significance value of 0.033. The results of the second hypothesis test show that there is a very significant relationship between the level of self disclosure and the level of achievement of the Terangbangsa FC U-18 players with a significance value of 0,000 with a correlation coefficient of -0.126. This, in line with the personality theory used, where self disclosure has a relationship with player achievment.